The impact of women's empowerment on their entrepreneurship intention in the Saudi food industry - Osama H. M. Hassan; Abu Elnasr E. Sobaih; Ibrahim A. Elshaer (Journal of Risk and Financial Management, 2022)
This study takes a novel attempt to examine the impact of women's empowerment in the Kingdom of Saudi Arabia, which has been prioritized recently by the country's leadership as a part of the Saudi Vision 2030, on women's intention towards entrepreneurship. A pre-examined survey was directed to the Saudi women working in KSA's food and beverage businesses. The structural equation modeling results showed a significant positive impact of psychosocial, economic, and political empowerment on Saudi women's intention to engage in entrepreneurship activities. However, the results confirmed a significant negative influence of social empowerment on entrepreneurship intentions. This is because Saudi women did not perceive the proper social empowerment by their community, which negatively influenced their entrepreneurship intention. Hence, interventions by decision-makers are crucial to adopt a media campaign regarding gender equality and the vital contribution of women in the labor market and entrepreneurship. Other implications were discussed for scholars and decision-makers.
Keywords: 650; economic empowerment; psychological empowerment; entrepreneurial intention; Kingdom of Saudi Arabia; political empowerment; social empowerment; women's empowerment